The effects of tutorial feedback type on pre-service teachers’ choice of feedback type in their development of learning objects - Çeken, Burç. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
This study aims to investigate the effect of different knowledge representation types in feedback presented in learning object (LO) development tutorials on the quality of pre-service teachers’ LOs as well as the representation type of feedback used in authoring the LO. The study, with a post-test only quasi-experimental design in nature, investigated six types of feedback representation: text, audio, video, video with text, video with audio, and video with audio and text feedback. Pre-service teachers’ (n=202) feedback preferences were collected with a questionnaire prior to the experiments. They then, studied how to develop LOs in an authoring environment, Articulate, in six different tutorials for seven weeks. The tutorials were identical in terms of teaching how to develop LOs, but were different in terms of the feedback provided. Pre-service teachers were assigned to one of the experiment groups by the researcher. Learning objects developed by pre-service teachers were assessed using the Learning Object Review Instrument (LORI). Analysis of the data showed that feedback presented by video was the most effective feedback representation type, based on both overall scores and feedback quality scores of LOs developed by the pre-services teachers. Additionally, interaction between feedback types presented by the LO development tutorial and pre-service teachers’ actual use of feedback in authoring LOs was not meaningful. The study compares findings with similar studies presented in the literature.
Keywords: Educational innovations.; Teaching -- Aids and devices.